Structure and function relationship of OqxB efflux pump from Klebsiella pneumoniae - Bharatham, Nagakumar; Bhowmik, Purnendu; Aoki, Maho; Okada, Ui; Sharma, Sreevalli; Yamashita, Eiki; Shanbhag, Anirudh P.; Rajagopal, Sreenath; Thomas, Teby; Sarma, Maitrayee; Narjari, Riya; Nagaraj, Savitha; et al. (Nature communications, 2021)
OqxB is an RND (Resistance-Nodulation-Division) efflux pump that has emerged as a factor contributing to the antibiotic resistance in Klebsiella pneumoniae . OqxB underwent horizontal gene transfer and is now seen in other Gram-negative bacterial pathogens including Escherichia coli , Enterobacter cloacae and Salmonella spp ., further disseminating multi-drug resistance. In this study, we describe crystal structure of OqxB with n-dodecyl-β-D-maltoside (DDM) molecules bound in its substrate-binding pocket, at 1.85 Å resolution. We utilize this structure in computational studies to predict the key amino acids contributing to the efflux of fluoroquinolones by OqxB, distinct from analogous residues in related transporters AcrB and MexB. Finally, our complementation assays with mutated OqxB and minimum inhibitory concentration (MIC) experiments with clinical isolates of E. coli provide further evidence that the predicted structural features are indeed involved in ciprofloxacin efflux. OqxB is an RND (Resistance-Nodulation-Division) transporter that contributes to the antibiotic resistance in Klebsiella pneumoniae . Here, the authors report structural and functional characterization of OqxB, with insights into its substrate binding pocket and the role in fluoroquinolone resistance.